Chromosomal and genic sterility of hybrid type in mice and men - Forejt, J (Experimental and clinical immunogenetics, 1985)
Three mouse models of male-limited, hybrid-type sterility are available: the sterility controlled by the T-t genetic complex, the hybrid sterility system including the Hst-1 gene, and the sterility of carriers of various chromosomal anomalies. A large body of experimental evidence has been gathered on the nonrandom attraction between X chromosome and rearranged autosomes in meiosis of carriers of various male-sterile chromosomal rearrangements in mice and men. A hypothesis is evaluated relating the X-autosomal interaction to spermatogenic breakdown. New data on the structure of t haplotypes indicate the presence of chromosomal inversions, and this might point to a chromosomal type of sterility of tx/ty hybrids. Gene hybrid sterility-1 is responsible for different fertility of male hybrids between certain laboratory and wild mice. The availability of wild mice (Mus musculus) derived inbred strains PWB, PWD, and PWK may facilitate further study of the hybrid sterility phenomenon in the mouse.
Keywords: Chromosome Disorders; Genes, Lethal; Genes, Recessive; mutantní kmeny myší; Male; geny recesivní; chromozomální poruchy; Infertility, Male; chromozomální aberace; spermatogeneze; Animals, Wild; divoká zvířata; Meiosis; translokace genetická; mužské pohlaví; Spermatogenesis; chromozom X; X Chromosome; Chromosome Aberrations; meióza; Animals; ženské pohlaví; zvířata; Hybridization, Genetic; myši; Translocation, Genetic; letální geny; hybridizace genetická; Mice; Female; mužská infertilita; Mice, Mutant Strains